Hubungan Pengetahuan dan Sikap Ibu yang Memiliki Bayi dengan Pemberian Imunisasi DPT-HB 1, 2, dan 3 di Puskesmas Mersip Tahun 2023 - Dwi Gustin Franciska; Irna Mayasari; Helti Lestari Sitinjak (Pusat riset dan Inovasi Nasional, 2025)
Complete basic immunization, including DPT-HB 1,2,3, plays a vital role in reducing infant morbidity and mortality from vaccine-preventable diseases. However, immunization coverage remains suboptimal, partly influenced by maternal knowledge and attitudes. This study aims to determine the relationship between mothers’ knowledge and attitudes and the provision of DPT-HB 1,2,3 immunization at Mersip Public Health Center in 2023. This quantitative research used a descriptive analytic method with a cross-sectional approach. The study involved 134 respondents selected through purposive sampling. Bivariate analysis using the chi-square test showed a significant relationship between mothers' knowledge (p = 0.000) and attitudes (p = 0.008) with the administration of DPT-HB 1,2,3 immunization. The study concludes that better maternal knowledge and positive attitudes are associated with a higher likelihood of complete DPT-HB 1,2,3 immunization for their babies. These findings highlight the need for enhanced health promotion by healthcare providers targeting mothers in the Mersip area.